Answer: ![\Large\boxed{(-4,~-3)~\text{and}~(-2,~1)}](https://tex.z-dn.net/?f=%5CLarge%5Cboxed%7B%28-4%2C~-3%29~%5Ctext%7Band%7D~%28-2%2C~1%29%7D)
Step-by-step explanation:
<u>Given the system of equation</u>
![1)~y=-(x+2)^2+1](https://tex.z-dn.net/?f=1%29~y%3D-%28x%2B2%29%5E2%2B1)
![2)~y=2x+5](https://tex.z-dn.net/?f=2%29~y%3D2x%2B5)
<u>Expand the parenthesis of the 1) equation</u>
![y=-(x+2)^2+1](https://tex.z-dn.net/?f=y%3D-%28x%2B2%29%5E2%2B1)
![y=-(x^2+4x+4)+1](https://tex.z-dn.net/?f=y%3D-%28x%5E2%2B4x%2B4%29%2B1)
![y=-x^2-4x-4+1](https://tex.z-dn.net/?f=y%3D-x%5E2-4x-4%2B1)
![y=-x^2-4x-3](https://tex.z-dn.net/?f=y%3D-x%5E2-4x-3)
<u>Current System</u>
![1)~y=-x^2-4x-3](https://tex.z-dn.net/?f=1%29~y%3D-x%5E2-4x-3)
![2)~y=2x+5](https://tex.z-dn.net/?f=2%29~y%3D2x%2B5)
<u>Substitute the y value of the 1) equation with the 2) equation</u>
![2x+5=-x^2-4x-3](https://tex.z-dn.net/?f=2x%2B5%3D-x%5E2-4x-3)
<u>Add ( x² + 4x + 3) on both sides</u>
![2x+5+(x^2+4x+3)=-x^2-4x-3+(x^2+4x+3)](https://tex.z-dn.net/?f=2x%2B5%2B%28x%5E2%2B4x%2B3%29%3D-x%5E2-4x-3%2B%28x%5E2%2B4x%2B3%29)
![2x+5+x^2+4x+3=0](https://tex.z-dn.net/?f=2x%2B5%2Bx%5E2%2B4x%2B3%3D0)
<u>Combine like terms</u>
![x^2+2x+4x+5+3=0](https://tex.z-dn.net/?f=x%5E2%2B2x%2B4x%2B5%2B3%3D0)
![x^2+6x+8=0](https://tex.z-dn.net/?f=x%5E2%2B6x%2B8%3D0)
<u>Factorize the quadratic equation</u>
![(x+4)(x+2)=0](https://tex.z-dn.net/?f=%28x%2B4%29%28x%2B2%29%3D0)
![x=-4~\text{or}~x=-2](https://tex.z-dn.net/?f=x%3D-4~%5Ctext%7Bor%7D~x%3D-2)
<u>Substitute the x values into one of the equations to find the y value</u>
![y=2x+5](https://tex.z-dn.net/?f=y%3D2x%2B5)
![y=2(-4)+5=-8+5=-3](https://tex.z-dn.net/?f=y%3D2%28-4%29%2B5%3D-8%2B5%3D-3)
![y=2(-2)+5=-4+5=1](https://tex.z-dn.net/?f=y%3D2%28-2%29%2B5%3D-4%2B5%3D1)
<u>Therefore, the two solutions are:</u>
![\Large\boxed{(-4,~-3)~\text{and}~(-2,~1)}](https://tex.z-dn.net/?f=%5CLarge%5Cboxed%7B%28-4%2C~-3%29~%5Ctext%7Band%7D~%28-2%2C~1%29%7D)
Hope this helps!! :)
Please let me know if you have any questions